Measurement of Air Bubbles Concentration in the Water by Means of Digital Image Processing - Vaidelienė, A.; Tervydis, P. (Elektronika ir Elektrotechnika, 2013)
While liquid flux are falling on air and water boundary, the entrainment of air is below this surface. Water aeration takes place and it‘s range is defined by the the concentration of formed bubbles. This paper suggests to measure concentration of air bubbles using digital image processing. For analysis of digital camera images library Python 2.7 was used.DOI: http://dx.doi.org/10.5755/j01.eee.19.4.1846